Recht auf Reparatur Vertragliche Umsetzung und Herausforderungen für das Handwerk - Arnold, Stefan (Wirtschaft und Recht für Mittelstand und Handwerk, 2024)
The EU wants to promote repairs and establish a "right to repair" to make the law more sustainable. The book uncovers incentives of the current law that are hostile to repair and detrimental to sustainability. It critically analyses the planned innovations and describes their consequences for the craft sector. The book shows that more ambitious measures are needed to effectively promote repairs. Among other things, it argues for a fundamental reform of the Directive 2019/771, a significant extension of the right to repair and substantial improvements regarding access to spare parts. At the same time, it explains the potential of measures outside contract law and addresses the relationship of sustainability, law and politics.